Severe Eosinophilic Syndrome: Highly Unlikely Associated with the Use of Probiotic Supplements! - Arthur C. Ouwehand; Ger T. Rijkers (Case Reports in Rheumatology)
A recent report in this journal suggested a causal relation between probiotic consumption and eosinophilia. In our opinion, the data presented does not suggest such a relationship. The two described eosinophilia cases have not been shown to be caused by infection and certainly not by probiotic infection. The consumed probiotics could not be retrieved in shops, so their identity remains unknown. Furthermore, the alleged consumption took place 2–4 weeks prior to the onset of the symptoms; during such time period, probiotics tend to have disappeared from the intestine. Because most probiotic health benefits are strain specific, also potential risks are strain specific. Thus, generalizing a risk to probiotics as a class is incorrect. We do, however, agree with the authors of the case report that quality control of probiotics should be rigorous. We also do not dispute that there may be certain risk groups (e.g. severely immune-compromised patients), where probiotic use should be carefully monitored. In conclusion, the data presented in the case report do not indicate that specific probiotics strains might cause eosinophilia.